Students’ Problem on Mastery of Islamic Religious Education Subject in Pandemic and Implications for the Curriculum Completeness and Competence Quality - Dini Himmatul Ulya; Raharjo, Raharjo; Ikhrom, Ikhrom (Pedagogia : Jurnal Pendidikan, 2024)
Problems of learning Islamic Religious Education (PAI=Pendidikan Agama Islam) during the pandemic have been discussed a lot, but have not related much to the mastering PAI learning materials. The purpose of this study was to analyze the problem of student mastery in Islamic Religious Education during the Covid-19 pandemic. The analysis includes: a description of students' mastery of material problems and their implications for curriculum completeness and competence quality. This qualitative research relies on interview, observation, and documentation data. The research participants involved 30 students and 6 teachers at SDI Luqman al-Hakim, SDN Integrated Model, and SDN Sobontoro I Bojonegoro. The results showed that based on the learning outcomes document, all students had exceeded the passing grade. but based on interviews, they do not understand the material they have studied. The problem of students' mastery of Islamic Religious Education during the Pandemic period was in the form of low achievement of cognitive aspects, inaccessibility of affective and psychomotor aspects. In line with that, the problem of student mastery of the PAI material has an impact on the problem of curriculum completeness and the quality of student competence. The results of this study recommend the importance of supporting institutional infrastructure, teachers and parents at home.